STIGMA MASYARAKAT TENTANG HIV/AIDS DI DESA PINTU LANGIT JAE - Nasution, Nurul Hidayah; Ritonga, Sukhri Herianto (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
Human Immunodeficiency virus (HIV) is a virus that attacks the human immune system. HIV continues to be a global public health problem as it has claimed nearly 33 million lives worldwide. People often assume that people who are infected with HIV / AIDS are people whose behavior is not good and is often associated with immoral behavior. We often see discrimination in people with HIV/AIDS. This makes more and more people with HIV/AIDS (PLWHA) are reluctant to open up and don't want to get antiretroviral (ARV) treatment. The purpose of this research was to describe the community's stigma about HIV/AIDS in Pintu Langit Jae Village, Angkola Julu District, Padangsidimpuan City. This type of research is a qualitative research with a phenomenological design. The informants in this research consisted of key informants, namely the village head, the main informant, namely the village community and supporting informants, namely P2M officers at Pintu Langit Health Center. Data collection by in-depth interviews and documentation. Data processing starts from the stage of data collection, data reduction, data presentation and drawing conclusions. Data analysis qualitatively and described in descriptive form. The results showed that most of the villagers still had a negative stigma about HIV/AIDS. It is recommended for health workers to be more aggressive in providing counseling and socialization related to HIV/AIDS and PLWHA to the community by using health promotion media that are liked by the community.